2017
DOI: 10.7150/ijbs.19891
|View full text |Cite
|
Sign up to set email alerts
|

Linker Histone in Diseases

Abstract: The linker histone is a protein that binds with the nucleosome, which is generally considered to achieve chromatin condensation in the nucleus. Accumulating evidences suggest that the linker histone is essential in the pathogenesis of several diseases. In this review, we briefly introduce the current knowledge of the linker histone, including its structure, characteristics and functions. Also, we move forward to present the advances of the linker histone's association with certain diseases, such as cancer, Alz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 81 publications
1
14
0
Order By: Relevance
“…In contraction, PLOD3 is also closely related to EMT in our previous description, which further supports our conclusion. In addition, it is worth noting that HILS1 is also related to chromatin remodeling and transcriptional regulation [ 31 ], in view of its strong correlation with PLOD3 and the result of enrichment analysis, this may imply the potential role of PLOD3 in chromatin function.…”
Section: Discussionmentioning
confidence: 99%
“…In contraction, PLOD3 is also closely related to EMT in our previous description, which further supports our conclusion. In addition, it is worth noting that HILS1 is also related to chromatin remodeling and transcriptional regulation [ 31 ], in view of its strong correlation with PLOD3 and the result of enrichment analysis, this may imply the potential role of PLOD3 in chromatin function.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in endocrine and neuronal cells, nuclear H1.0 as well as H3 core histone, and lamin interact with a nuclear fraction of the cellular prion protein [ 53 ]. From a more general point of view, many authors have found extranuclear [ 54 ], and even extracellular H1 (see Section 5 ) [ 55 ].…”
Section: H10 Linker Histone In Mammals: Structural Peculiarities mentioning
confidence: 99%
“…Alzheimer's disease, infertility and autoimmune diseases (Ye et al, 2017). The H4K20Me3 studies come up with new hypotheses -(A) NRL-dependent effect of H4K20Me3 on chromatin compaction; (B) H4K20Me3 acts as binding platform for specific protein factors regulating chromatin architecture.…”
Section: Discussionmentioning
confidence: 99%
“…Structural studies of chromatosome came up with multiple debating models in terms of linker histone localization and interaction with the nucleosome (Bednar et al, 2017;Brown et al, 2006;Zhou et al, 2015). The decrease in linker histone level is closely related to multiple diseases (Ye et al, 2017). Besides, the effect of linker histone on chromatin compaction is influenced by NRLs (Routh et al, 2008).…”
Section: Objectivesmentioning
confidence: 99%